PENINGKATAN KEMAMPUAN SISWA MEMBACA PERMULAAN DI KELAS I DI SDN. NO 3 MELI DENGAN MENGGUNAKAN METODE LATIHAN TERBIMBING - MAS’AYU, MAS’AYU (Jurnal Kreatif Tadulako Online, 2018)
This research aimed at increasing studentsâ ability in Pre-reading activity at the first grade students of SDN No.3 Meli through guided method. The design of this research was Classroom Action Research (CAR). The sample of the research was 20 students of the first graders of SDN No.3 Meli; 9 males and 11 females. The research was conducted in two cycles; the first cycle only reached 60%, while the second one was 95%. The standard of classical learning achievement was 80%. This result was gained from observation result of learning process based on observation checklists, and it showed that the second cycle was successful since it fulfilled the requirement of research standard. Then, the researcher concluded that the use of Guided Method can increase the ability of the first grade students of SDN No.3 Meli in Pre-reading activity. Â  Keywords: Pre-reading activity, Guided Method.